CD38 Enhances TLR9 Expression and Activates NLRP3 Inflammasome after Porcine Parvovirus Infection - Yi Zheng; Yixuan Xu; Weimin Xu; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; Yifei Lang; Shan Zhao; Rui Wu (Viruses, 2022)
(1) Background: Porcine Parvovirus (PPV) is a single-stranded DNA virus without envelope which causes great harm in relation to porcine reproductive disorders in clinic. Cluster of Differentiation 38 (CD38) is a transmembrane protein widely existing in mammals. Its various functions make it a very popular research object, including in the viral infection field. (2) Methods: Western blotting and an EdU Cell Proliferation Kit were used to evaluate the effect of CD38-deficient cells. Relative quantitative real-time RT-PCR was used to detect the transcription levels of cytokines after PPV infection. The renilla luciferase reporter gene assay was used to verify the activation function of CD38 on downstream factors. The fluorescence probe method was used to detect the level of intracellular reactive oxygen species (ROS). (3) Results: This study found that the loss of CD38 function inhibited the up-regulated state of Toll-like Receptor 9 (TLR9), Interferon-α (IFN-α), and Myxovirus Resistance 1 (Mx1) after PPV infection. The luminescence of the group transfected with both CD38 expression plasmid and TLR9 promoter renilla luciferase reporter plasmid was significantly up-regulated compared with the control, suggesting that CD38 may activate the promoter of TLR9. In addition, CD38 deficiency not only activated the transcription of Sirtuin-1 (SIRT1), but also inhibited ROS level and the transcription of NLR Family Pyrin Domain Containing 3 (NLRP3). (4) Conclusion: (i) CD38 may participate in the TLR9/IFN-α/Mx1 pathway by activating the expression of TLR9 after PPV infected PK-15 cells; (ii) CD38 may activate the NLRP3/CASP1 pathway by increasing ROS level; (iii) CD38 deficiency activates the expression of SIRT1 and can prevent the normal proliferation of PPV.